Rašinovac near Ždrapanj (northern Dalmatia) – An early neolithic site (Archaeologia Adriatica, 2020)
This paper presents the results from an archaeological excavation at the Neolithic site of Rašinovac, near Ždrapanj in the Piramatovci Valley (in the hinterland of the town of Skradin in Northern Dalmatia). This previously unknown site was test excavated in 2013 when a 2x2-metre trench was opened to determine the site’s stratigraphy and chronology. Excavations suggested that Rašinovac was a single-layer open-air settlement and subsequent analyses of the material culture (mostly pottery and chert) confirmed that it was an Impressed Ware site. Two radiocarbon dates also reveal that Rašinovac is among the earliest known Early Neolithic sites in the region (first century of the 6th millennium BC).
Keywords: Rašinovac; Early Neolithic; Impressed Ware; settlement; Northern Dalmatia